2018
DOI: 10.1186/s13256-018-1864-z
|View full text |Cite
|
Sign up to set email alerts
|

Extracorporeal membrane oxygenation in aluminum phosphide poisoning in Nepal: a case report

Abstract: BackgroundAluminum phosphide is a very common suicide agent in developing countries like Nepal. Due to the unavailability of a specific antidote, mortality is very high because the phosphine molecule that is formed leads to inhibition of the cytochrome oxidase enzyme system in mitochondria. Extracorporeal membrane oxygenation provides life-saving support to the cardiovascular and respiratory systems until the deadly poison is eliminated from the body.Case presentationWe encountered one case of 67-year-old Asia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 10 publications
0
11
0
1
Order By: Relevance
“…[26][27][28] The past decade has seen a parallel increase in the use of ECMO support in phosphine toxicity, and although individual cases have been reported from Israel, USA and Germany, most case series have been published from developing countries. 8,[29][30][31][32][33] The largest series was an Indian retrospective observational study which identified 83 patients during this decade with severe AlP toxicity, and reported a mortality of 87% in those who did not receive ECMO, compared with only 33% mortality in those who did receive ECMO, despite the latter having worse baseline left ventricular EF and pH <7. The ECMO support period in all these series was typically less than seven days, and most people had normal recovery.…”
Section: Discussionmentioning
confidence: 99%
“…[26][27][28] The past decade has seen a parallel increase in the use of ECMO support in phosphine toxicity, and although individual cases have been reported from Israel, USA and Germany, most case series have been published from developing countries. 8,[29][30][31][32][33] The largest series was an Indian retrospective observational study which identified 83 patients during this decade with severe AlP toxicity, and reported a mortality of 87% in those who did not receive ECMO, compared with only 33% mortality in those who did receive ECMO, despite the latter having worse baseline left ventricular EF and pH <7. The ECMO support period in all these series was typically less than seven days, and most people had normal recovery.…”
Section: Discussionmentioning
confidence: 99%
“…Other authors suggested the use of intralipid emulsion to neutralize the dissolved circulating phosphine [ 14 ]. Moreover, in cases of severe hemodynamic collapse not responding to usual or novel approaches, recourse to extracorporeal membrane oxygenation (ECMO) or intra-aortic balloon pump is increasingly reported [ 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…57 ECLS was successfully used to manage AlP-poisoned patients with shock non-responding to inotropes/ vasopressors (Table 5). [56][57][58][59] Lactate concentrations ranged from 8.8 to 47 mmol/L, and all patients survived. All reported single cases presented severely depressed cardiac function with 20%-30% LVEF.…”
Section: Ecls To Treat Aip-poisoned Patientsmentioning
confidence: 99%